The Use of Music and Music Therapy in Ameliorating Depression Symptoms and Improving Well-Being in Nursing Home Residents With Dementia - Ray, Kendra D.; Götell, Eva (Frontiers in Medicine, 2018)
Background: Studies have shown music therapy can improve depression symptoms in dementia and the use of music activities show promise to have positive impacts on wellbeing. However, few studies show the influence of a music intervention led by certified nursing assistants (CNAs) trained by music therapists to address depression symptoms and wellbeing in individuals with dementia. Methods: Credentialed music therapists (1) administered 2-weeks of music therapy, (2) a 3-days training to CNAs, (3) followed by 2-weeks of music activities, singing and music-with-movement, led by CNAs for 62 nursing home residents with moderate dementia, (4) then measured depression symptoms using the Cornell Scale for Depression. We obtained video consent for 26 of the 62 residents who were video recorded receiving CNA-led music-based caregiving activities. Using the Music in Dementia Scale, over 200 h of video data was observed and raters measured changes in well-being, e.g., levels of enjoyment, mood and engagement in the residents, during the CNA facilitated music activities. Results: A repeated measures ANOVA revealed that mean depression scores differed statistically significantly between time points, p ≤ 0.001. Residents' baseline depression symptoms significantly declined following 2 weeks of music therapy, p ≤ 0.001, increased during a 2-weeks wash-out period, p = 0.389, but appeared to stabilize following the 2-weeks music activity, p = 1.00. A video analysis and paired sampled t-test demonstrated a significant improvement in wellbeing in residents who engaged in music with movement, p = 0.003. Wellbeing improved slightly, but not significantly for residents who participated in the singing intervention, p = 0.165. Conclusion: Findings suggest that music therapy can significantly decrease depression symptoms in nursing home residents with dementia. Music activities designed by music therapists and facilitated by CNAs may help sustain the reduction of depression symptoms and improve wellbeing in nursing home residents with moderate to severe dementia.